EFFECT OF SEED PRIMING ON FIELD PERFORMANCE AND SEED YIELD OF SOYBEAN [GLYCINE MAX (L.) MERILL] VARIETIES - N. G. CHAVAN,; G. B. BHUJBAL,; M. R. MANJARE, (The Bioscan, 2014)
A study was conducted to determine the importance seed priming on field performance and seed yield of Soybean. There were two varieties viz., Phule Kalyani and JS-335 while six priming treatments viz., Control (unprimed seeds), Hydropriming, KCl @10 ppm, CaCl2.2H2O @ 0.5 %, KH2PO4 @ 50 ppm and GA3 @ 20 ppm. The variety Phule Kalyani primed with CaCl2.2H2O (0.5%) were superior in plant height, number of branches, number of pods per plant, number of seeds per pod, seed yield per hectare over those raised from the variety JS335.